Two cases with Plummer–Vinson syndrome in the 21st century - Gültepe, İlhami and Başaranoğlu, Metin (Turkish Journal of Gastroenterology, 2016)
Abstract Plummer–Vinson syndrome (PVS) is characterized by the presence of postcricoid dysphagia, iron deficiency anemia, and upper esophageal web. This syndrome is now a rare condition because of the improvement in nutritional status and increased awareness regarding iron deficiency anemia and the early diagnosis and easy treatment of this anemia or underlying causes. In this presentation, we report two middle-aged female patients with PVS and briefly review the literature.